Diet and physical exercise as key players to tackle MASLD through improvement of insulin resistance and metabolic flexibility - Mambrini, Sara Paola; Grillo, Antonio; Colosimo, Santo; Zarpellon, Francesco; Pozzi, Giorgia; Furlan, Davide; Amodeo, Gabriele; Bertoli, Simona (Frontiers in Nutrition, 2024)
Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) has emerged as a prevalent health concern, encompassing a wide spectrum of liver-related disorders.Insulin resistance, a key pathophysiological feature of MASLD, can be effectively ameliorated through dietary interventions. The Mediterranean diet, rich in whole grains, fruits, vegetables, legumes, and healthy fats, has shown promising results in improving insulin sensitivity. Several components of the Mediterranean diet, such as monounsaturated fats and polyphenols, exert anti-inflammatory and antioxidant effects, thereby reducing hepatic steatosis and inflammation. Furthermore, this dietary pattern has been associated with a higher likelihood of achieving MASLD remission.In addition to dietary modifications, physical exercise, particularly resistance exercise, plays a crucial role in enhancing metabolic flexibility. Resistance exercise training promotes the utilization of fatty acids as an energy source. It enhances muscle glucose uptake and glycogen storage, thus reducing the burden on the liver to uptake excess blood glucose. Furthermore, resistance exercise stimulates muscle protein synthesis, contributing to an improved muscle-to-fat ratio and overall metabolic health.When implemented synergistically, the Mediterranean diet and resistance exercise can elicit complementary effects in combating MASLD. Combined interventions have demonstrated additive benefits, including greater improvements in insulin resistance, increased metabolic flexibility, and enhanced potential for MASLD remission. This underscores the importance of adopting a multifaceted approach encompassing dietary modifications and regular physical exercise to effectively manage MASLD.This narrative review explores the biological mechanisms of diet and physical exercise in addressing MASLD by targeting insulin resistance and decreased metabolic flexibility.